KONSEP SANAD DALAM PERSPEKTIF ILMU HADITS (Telaah terhadap Kualitas dan Kuantitas Hadits Nabi Muhammad Saw.) - Dozan, Wely; Turmuzi, Muhamad; Sugitanata, Arif (Jurnal El-Hikam, 2020)
The study of sanad in the perspective of hadith science is a basic concept that needs to be understood and analyzed again in Islamic studies. Sanad in the science of hadith is the basis or pathway narration of the hadith which has an important role in determining the quality and quantity of a hadith. The focus of this study is to try to provide a significant understanding of sanad in the science of hadith, then to apply it in the hadiths of the Prophet. Specifically, there are a number of basic concepts that are subject to research studies. Among them, First, explore the meaning of the term sanad in the hadith. Second, the urgency of sanad in the study of hadith. Third, understand the path of transmission and application of the quality and quantity of the Prophet's hadith. The research approach used is the study of literature that is to support solving problems both related to books, journals, articles and so on. The results of this study indicate that, sanad in the perspective of the science of hadith is a science that examines the origin of the narration of hadith and also to determine the quality and quantity of whether or not a hadith is accepted as hujjah in Islamic law.